Concentrating stabilized human urine using eutectic freeze crystallization for liquid fertilizer production. (15th April 2023) - Courtney, Caitlin; Randall, Dyllon G.
Abstract: Resource recovery from source-separated urine can be used to produce fertilizers and provide a more sustainable alternative to mineral fertilizers. Reverse osmosis can be used to remove up to 70% of the water in urine that has been stabilized with Ca(OH)2 and pre-treated with air bubbling. However, further water removal is limited because of membrane scaling and equipment operating pressure limitations. A novel hybrid eutectic freeze crystallization (EFC) and RO system was investigated as a method to concentrate human urine, whilst simultaneously crystallizing salt and ice under EFC conditions. A thermodynamic model was used to predict the type of salts that would crystallize, their associated eutectic temperatures, and how much additional water removal was required (using freeze crystallization) to reach eutectic conditions. This innovative work showed that at eutectic conditions, Na2 SO4 ∙10H2 O crystallizes simultaneously with ice in both real and synthetic urine, thus providing a new method to concentrate human urine for liquid fertilizer production. A theoretical mass balance of a hybrid RO-EFC process, including ice washing and recycle streams, showed that 77% of the urea and 96% of the potassium could be recovered with a 95% water removal. The final liquid fertilizer would have a composition of 11.5% N and 3.5% K, and 3.5 kg of Na2 SO4 ∙10H2 O could be recovered from 1000 kg of urine. Over 98% of the phosphorus would be recovered as calcium phosphate during the urine stabilization step. A hybrid RO-EFC process would require 60 kWh m −3 of energy, which is substantially less than other concentration methods. Graphical abstract: Image, graphical abstract